Improving the antioxidant and antibacterial activities of fermented Bletilla striata with Fusarium avenaceum and Fusarium oxysporum. Issue 1 (January 2015) - Dong, Jian-Wei; Cai, Le; Xiong, Jie; Chen, Xiu-Hua; Wang, Wei-Ying; Shen, Ni; Liu, Bei-Lei; Ding, Zhong-Tao
Highlights Bletilla striata was processed by pure strain fermentation for the first time. Fusarium avenaceum and Fusarium oxysporum might be effective in B. striata fermentation processing. UV–vis, FT-IR, and NMR spectra were effective in characterization of fermented B. striata.